(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
The introduction of the Long Term Evolution (LTE) technology in recent technologies has revolutionized Fourth Generation, 4G Network communication, allowing users to receive high-speed data up to 100 MHz. The problem of cyber-security has become a menace to consumers all around the globe. This article will go through the LTE security concept. The next generations of wireless networks, known as 4G, will completely replace 3rd generation networks. It will provide faster speeds and multimedia services that are entirely IP based. 4G refers to an integrated, worldwide network that will give customers with phone, data, and streaming multimedia services "Anytime, Anywhere." The smooth handoff, mobility management, security, and service across multiple integrated networks are all essential and demanding issues in 4G. Data security, hardware security, and user privacy and integrity are the most important security concerns for any wireless mobile device. Security flaws may be created by attackers or induced by incorrect device or network parameter settings. The paper explains the concept of security and why it is important to pay attention to it. This paper examines what 4G network technology is and some of the proposed solutions in order to fully understand the benefits and problems of successfully deploying 4G. The future aspects are this Network access security, which allows users to access the service in a safe and secure manner.